Child and adolescent psychiatry in the Far East: A 5‐year follow up on the Consortium on Academic Child and Adolescent Psychiatry in the Far East (CACAP‐FE) study. Issue 2 (24th December 2018) - Hirota, Tomoya; Guerrero, Anthony; Sartorius, Norman; Fung, Daniel; Leventhal, Bennett; Ong, Say H.; Kaneko, Hitoshi; Apinuntavech, Suporn; Bennett, Abang; Bhoomikumar, Jegannathan; Cheon, Keun‐Ah; Davaasuren, Oyunsuren; et al.
Abstract : Aim: Data pertaining to child and adolescent psychiatry (CAP) training systems are limited as extant research has mostly been derived from one‐time data collection. This 5‐year follow‐up survey collects updated information on CAP training systems in the Far East, allowing for the tracking of system changes over the past 5 years. Methods: Data were obtained from 18 countries, or functionally self‐governing areas, in the Far East, 17 of which were also included in the original study. An online questionnaire was completed by leading CAP professionals in each country. Questions were expanded in the present study to capture the contents of CAP training. Results: When compared to data from the original study, there has been progress in CAP training systems in the last 5 years. Specifically, there has been an increase in the number of countries with CAP training programs and national guidelines for the training. In addition, the number of CAP departments/divisions affiliated with academic institutions/universities has increased. Findings from 12 of 18 countries in the present study provide data on clinical contents. All informants of the present study reported the need for more child and adolescent psychiatrists and allied professionals. Conclusion: Despite progress in CAP training systems over the last 5 years, the need for more professionals in child and adolescent mental health care in all the relevant areas in this region have yet to be adequately addressed. Continued national efforts and international collaborations are imperative to developing and sustaining new CAP training systems while facilitating improvements in existing programs.